2008
DOI: 10.1080/07357900802074349
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of HOX, ErbB and IGFBP Family Gene Expression in Ovarian Cancer

Abstract: Utilizing microarray gene expression data in cancer research possesses the ability to identify deregulated cellular pathways involved in malignant development. This study investigated the relationships of three gene families, HOX, ErbB and IGFBP, with regard to the development of ovarian cancer. These families were of interest because of similar chromosomal locations and their deregulated expression in ovarian cancer. Higher level statistics were used to differentially analyze microarray data in 65 ovarian sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In the normal adult brain, most HOX genes are not expressed at all or are expressed at very low levels [13]. However, reports have demonstrated increased expression of HOX genes in brain tumors as well as other cancers from various organs [16, 26-32]. Murat et al reported coordinated data of HOX genes and treatment resistance in GBM samples [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the normal adult brain, most HOX genes are not expressed at all or are expressed at very low levels [13]. However, reports have demonstrated increased expression of HOX genes in brain tumors as well as other cancers from various organs [16, 26-32]. Murat et al reported coordinated data of HOX genes and treatment resistance in GBM samples [10].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that abnormal HOX gene expression may be involved in oncogenesis. Aberrant HOX gene expression has been noted in acute myeloid and mixed lineage leukemia (9, 13, 18), breast (29), cervical (34), non‐small cell lung (28), ovarian (6), prostate (42), skin (24) and thyroid cancers (38). The overexpression of HOX genes in MEPN combined with their potential oncogenic function suggests that the HOX family should be evaluated as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-6 was detected in 38 out of 41 ovarian cancers by immunohistochemistry, but it was not regulated by oestrogen in oestrogen-responsive cancer cells in vitro [79]. A single microarray study showed that IGFBP-6 mRNA levels were lower in ovarian cancer tissue compared with non-cancerous tissue [160]; this may result in increased IGF-II action, but IGFBP-6 levels were not confirmed in an independent assay. Two studies of women with ovarian cancer showed discrepant results with one showing increased serum IGFBP-6 levels [161] and the other showing lower levels [162].…”
Section: Ovarian Cancermentioning
confidence: 93%